Professional Culture of the Manager of an Out-of- School Educational Institution as an Object of Scientific Analysis - Inna Naumchuk (Pedagogical Discourse, 2016)
In the article the author carried out a scientific systematic analysis of the source base study of the problem of professional culture of a head of an out- of- school educational institution, optimal ways of its formation and development in the system of postgraduate education. Different scientific definitions of the essence of concepts «profession» and «professional culture» were examined. The author analyzed the different classifications of occupations: on the nature of labor (mental, physical),on the level and nature of the necessary qualifications (for workers),on the objects of labor (human - nature, people - machinery, man - man, man - a sign system, human - artistic image) , on the means of labor and so on. We studied ambiguity of the concept of «culture», which is explained by the breadth of the term used in psychological and educational research: culture as a value, culture as an activity, as a creative culture. On the basis of summarizing the work of domestic and foreign scientists that investigate the professional culture, the characteristics of the main directions of research on the subject were described, namely, the disclosure of the general principles of professional culture; study of the major problems of formation of the personality of a teacher as the subject of activity; the integrity of his professional and pedagogical training; coverage of certain aspects of professional culture of a teacher. The article focuses on scientific approaches to determining the structure of the professional culture, justifying its components. On the basis of analysis and generalization of scientific definitions of the term «professional culture», it was formulated the own interpretation of the definition «professional culture of a head of an out- of school educational establishment», which is understood as the degree of assimilation and the manifestation of the systems of social and professional values and ideals, formed in the process of professional socialization, characterizing quality of the level of administrative, educational, managerial, economic, communicative and other activities of a manager.Key words: profession, culture, professional culture, structure of professional culture, professional competence, manager of an out-of -school educational institution.